Conformational Selection in Glycomimetics: Human Galectin‐1 Only Recognizes syn‐Ψ‐Type Conformations of β‐1, 3‐Linked Lactose and Its C‐Glycosyl Derivative. Issue 43 (17th September 2013) - Vidal, Paloma; Roldós, Virginia; Fernández‐Alonso, María del Carmen; Vauzeilles, Boris; Bleriot, Yves; Cañada, F. Javier; André, Sabine; Gabius, Hans‐Joachim; Jiménez‐Barbero, Jesús; Espinosa, Juan Félix; Martín‐Santamaría, Sonsoles
Abstract The human lectin galectin‐1 (hGal‐1) translates sugar signals, that is, β‐galactosides, into effects on the level of cells, for example, growth regulation, and has become a model for studying binding of biopharmaceutically relevant derivatives. Bound‐state conformations of Galβ‐C‐(1→3)‐Glcβ‐OMe (1) and its βGal‐(1→3)‐βGlc‐OMe disaccharide parent compound were studied by using NMR spectroscopy (transferred (TR)‐NOESY data), assisted by docking experiments and molecular dynamics (MD) simulations. The molecular recognition process involves a conformational selection event. Although free C‐glycoside access four distinct conformers in solution, hGal‐1 recognizes shape of a local minimum of compound 1, the syn‐Φ/syn‐Ψ conformer, not the structure at global minimum. MD simulations were run to explain, in structural terms, the observed geometry of the complex.